Functional analysis of Ssc1 and Iba57 proteins in Trypanosoma brucei - Skalický, Tomáš (Jihočeská univerzita, 2011)
Aim of this thesis was to shed light on the function(s) of Iba57 and Ssc1 proteins in both life cycle stages of T. brucei using RNA interference. Depletion of Ssc1 resulted in severe grow phenotype, decrease in activities of iron-sulphur cluster-containing enzyme aconitase but no increase in oxidative stress sensitivity or accumulation of ROS in mitochondrion. Down regulation of Iba57, specialized maturation factor of aconitase and homoaconitase, lead to depletion of aconitase, destabilization of Isa1 and increased sensitivity to oxidative stress and accumulation of ROS in both stages.
Functional analysis of Ssc1 and Iba57 proteins in Trypanosoma brucei
Keywords: Iba57; Ssc1; chaperone; Trypanosoma brucei; Fe-S cllusters; functional analysis; RNA interference; oxidative stress; mitochondrion; Iba57; Ssc1; chaperone; Trypanosoma brucei; Fe-S cllusters; functional analysis; RNA interference; oxidative stress; mitochondrion